Design and Analysis of a Dynamic Splint Based on Pulley Rotation for Post-Stroke Finger Extension Rehabilitation Device - Emzain, Zakki Fuadi; Huang, Shyh-Chour; Yang, Yu-Sheng; Qosim, Nanang (Jurnal Rekayasa Mesin, 2020)
The presence of rehabilitation tools is essential to more rapidly cure hand muscle disorders of people affected by stroke. One of the tools is a dynamic splint that is fit-sized, lightweight, comfortable to wear, and easy to operate. The paper proposes the design and analysis of new dynamic splints based on pulley rotation as a rehabilitation device for finger extension after stroke. This device consists of the main splint, the pulley, the locker, the finger handles, the ball bearing, and the fishing line. To lock and stop pulley turning, the locking system is designed to complement it which is also the most important mechanical segment. The shear stress of the pulley was 0.026 N/mm2. The deformation, stress, and strain energy of the locking system section were analyzed by the finite element method. The results showed that the deformation distribution around the locker section was at 0.1-0.15 mm intervals. The maximum stress 25.0786 MPa, which is still inferior to the yield strength of ABS Material (28.5 MPa). The safety factor of the structure is about n = 1.14. The largest strain energy was 0.2856 mJ at the same place as with the maximum stress which was close to the conical end of the locker. The correlation between stress-strain energy and moment was linear as well. In future work, a prototype will be fabricated using 3D printers, and it will be applied to the stroke patient. In addition, the therapies will be involved to assess the improvement of the finger extension of stroke patients.